HUBUNGAN PERHATIAN ORANG TUA TERHADAP MOTIVASI BELAJAR ANAK DALAM MENGERJAKAN PERKERJAAN RUMAH - Dede Septyan Sadewo; rosmalah rosmalah; Makmur Nurdin (Universtas Negeri Makassar, 2021)
This study is a quantitative study with a correlation model that aims to determine the significant relationship between parents' attention to learning motivation in doing homework at SD Inpres 12/79 Macanang. The population in this study were high grade students of SD Inpres 12/79 Macanang with 165 students while the sample was 84 people. Data collection was carried out by means of a questionnaire. Data analysis techniques with descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, it was obtained that parents' attention had an average of 85.6% and a percentage of 85.6% in the very good category and the average children's learning motivation in doing homework was 85.28 and the percentage was 85.28% with the category very good. Based on the results of inferential statistical analysis shows the value of tcount (6.765 greater (>) the value of ttable (1.66365) at a significance level of 5%. Thus, H0 is rejected and H1 is accepted. From the results of the study, it can be concluded that a significant relationship between parents' attention to motivation to learn in doing homework SD Inpres 12/79 Macanang.